2021
DOI: 10.21203/rs.3.rs-802948/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation of the Effect of Intermetallic Compounds on the Mechanical and Electrical Properties of Friction Stir Welded Al and Cu Busbar for Battery Pack Applications

Abstract: Aluminium and copper (Al-Cu) busbar is widely used as a core component in Lithium-Ion (Li-ion) batteries. The Al-Cu busbar is challenging to fabricate with the traditional welding processes because of its high thermal conductivity. In the present study, the Al-Cu busbar is fabricated using the friction stir welding method. The effect of temperature and vibration generated during the welding process on the formation of intermetallic compounds (IMCs) is studied by using the effective formation model and found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…When Al-Cu is welded without interlayer either through butt configuration or lap configuration, the IMCs formed are AlCu, 2,7,11,16,20,22,26 Al 2 Cu, 2,7,11,16,[20][21][22]26,110,111,113,114 Al 2 Cu 3 , 7,11,20,22,112 Al 3 Cu 4 , 20,22 and Al 4 Cu 9 . 7,11,12,16,20,22,26,109,[111][112][113][114] Mechanical properties of FSWed Al-Cu joints Sahu et al investigated the hardness of dissimilar friction stir welded Al-Cu joints. They reported that the bottom layer's hardness was higher than the upper and middle layers, as well as the thickness of the weld, due to the faster cooling rate and the presence of different IMCs.…”
Section: Microstructures and Imcsmentioning
confidence: 99%
See 3 more Smart Citations
“…When Al-Cu is welded without interlayer either through butt configuration or lap configuration, the IMCs formed are AlCu, 2,7,11,16,20,22,26 Al 2 Cu, 2,7,11,16,[20][21][22]26,110,111,113,114 Al 2 Cu 3 , 7,11,20,22,112 Al 3 Cu 4 , 20,22 and Al 4 Cu 9 . 7,11,12,16,20,22,26,109,[111][112][113][114] Mechanical properties of FSWed Al-Cu joints Sahu et al investigated the hardness of dissimilar friction stir welded Al-Cu joints. They reported that the bottom layer's hardness was higher than the upper and middle layers, as well as the thickness of the weld, due to the faster cooling rate and the presence of different IMCs.…”
Section: Microstructures and Imcsmentioning
confidence: 99%
“…The higher the welding speed, the more vibration was generated, resulting in the formation of larger Cu-rich intermetallic Al 4 Cu 9 , which improved tensile strength and electrical characteristics. 112 Muhammad and Wu produced the joints of Al-Cu by placing Al in RS and AS and named as I joint and II joint, respectively. They compared the electrical conductivity with UTS of different type joints formed by FSW and UVaFSW as shown in Supplementary Figure 39, and their given results are as follows 124 :…”
Section: Electrical Analysis Of Fswed Al-cu Jointsmentioning
confidence: 99%
See 2 more Smart Citations